General Physical Properties of Rainfed Soils in the Northern Part of the Turkistan Range - Jabborovich, Mamaraimov Dilshod; Amirqulovich, Musurmanov Alisher (American Journal of Biology and Natural Sciences, 2026)
This article examines the general physical properties of rainfed (boghar) soils in the northern part of the Turkestan mountain range. It has been established that over the past period, the general physical properties of these soils have undergone certain changes. The main reasons for this include climate change and the impact of anthropogenic factors, namely the implementation of agrotechnical measures, continuous grazing of large and small ruminants on virgin lands, as well as the use of heavy agricultural machinery, which has negatively affected soil bulk density and total porosity.